INCREASING THE ROLE OF STRATEGIC MANAGEMENT ACCOUNTING AND TAX AWARENESS IN FORMING TAX COMPLIANCE OF MSMES WITH A MODERATING INFLUENCE ON ORGANIZATIONAL PERFORMANCE - Hutagalung, Dhaniel; Sukriyah, Sukriyah (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) significantly contribute to Indonesia's national economy, despite facing substantial challenges, including low tax compliance rates. Most previous studies have focused their analysis on tax awareness factors, leaving an important gap regarding the role of Strategic Management Accounting (SMA). This study aims to address this gap by comprehensively analyzing the influence of SMA and tax awareness on MSME tax compliance. Specifically, this study also examines the role of organizational performance as a moderating variable in this relationship. A quantitative method was used, involving 300 MSME actors as respondents through a survey conducted in three strategic provinces: DKI Jakarta, Banten, and West Java. The data were processed and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) technique. Empirical results indicate that SMA and tax awareness independently have a significant positive effect on increasing MSME tax compliance. Another crucial finding is that organizational performance significantly moderates the effect of AMS on compliance, but this moderating role is not significant in the relationship with tax awareness. These findings emphasize the importance of integrating a measurable managerial approach (through AMS) with awareness factors to achieve an optimal and sustainable level of MSME tax compliance.